STRATEGY TO REVIVE AGRICULTURAL RICE TOURISM IN PEMATANG JOHAR VILLAGE - Fahmi Ashari S Sihaloho; Imamul Khaira; Muammar Rinaldi (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
The development of agrotourism is believed to increase public awareness of the importance of preserving agricultural land resources. Furthermore, agrotourism development can also aid in preserving local cultural wisdom in the vicinity of the agrotourism area. Sawah Pematang Johar Agrotourism is one of the agrotourism sites developed by the community as a means to boost the village economy. However, over time, there has been a decline in tourist activities at the Pematang Johar Agrotourism site, requiring a strategy for sustainable development. This study is a descriptive literature review using data sources from various articles published in the last 10 years, obtained from reputable national and international journals, as well as secondary data from government websites. The content of this writing represents the author's thoughts on strategies to revive Sawah Desa Pematang Johar agrotourism as a backbone for the local economy. Data in this research is gathered from books, journal articles, and direct field observations, structured to provide solutions and strategies to reinvigorate Sawah Pematang Johar Agrotourism Post-Covid-19. It is hoped that this article will offer solutions to the decline in the local economy of Pematang Johar Village, Deli Serdang Regency, due to a decrease in tourists visiting the Pematang Johar Agrotourism site.